Salivary cortisol in low dose (1 µg) ACTH test in healthy women: comparison with serum cortisol - Šimůnková, Kateřina; Hampl, Richard; Hill, Martin; Doucha, Jindřich; Stárka, Luboslav; Vondra, Karel (Physiological research, 2007)
To date, a single report has appeared on the use of salivary cortisol for adrenal function testing with a low dose ACTH, although 1 µg has become preferred as a more physiological stimulus than the commonly used 250 µg ACTH test. Our present study was aimed to obtain physiological data on changes of free salivary cortisol after 1 µg ACTH stimulation. This approach was compared with the common method based on the changes of total serum cortisol. Intravenous, lowdose ACTH test was performed in 15 healthy women (aged 22-40 years) with normal body weight, not using hormonal contraceptives, in the follicular phase of the menstrual cycle. Blood and saliva for determination of cortisol were collected before ACTH administration and 30 and 60 min after ACTH administration. Basal concentration of salivary cortisol (mean ± S.E.M., 15.9±1.96 nmol/l) increased after 1 µg ACTH to 29.1±2.01 nmol/l after 30 min, and to 27.4±2.15 nmol/l after 60 min. The differences between basal and stimulated values were highly significant (p<0.0001). The values of salivary cortisol displayed very little interindividual variability (p<0.04) in contrast to total serum cortisol values (p<0.0001) A comparison of areas under the curve (AUC) related to initial values indicated significantly higher AUC values for salivary cortisol than for total serum cortisol (1.89±0.88 vs. 1.22±0.19, p<0.01). Correlation analysis of serum and salivary cortisol levels showed a borderline relationship between basal levels (r=0.5183, p=0.0525); correlations after stimulation were not significant. Low-dose ACTH administration appeared as a sufficient stimulus for increasing salivary cortisol to a range considered as a normal adrenal functional reserve.
Keywords: adrenokortikotropní hormon; ženy; sliny; Saliva; menstruační cyklus; Women; Salivary Glands; financování organizované; Menstrual Cycle; Adrenal Cortex Function Tests; adrenokortikální funkční testy; Financing, Organized; Transcortin; Hydrocortisone; transkortin; hydrokortison; slinné žlázy; Adrenocorticotropic Hormone